MEASUREMENTS AND INTERPRETATION OF GRAVITY ANOMALY IN AND AROUND ROSS ISLAND, ANTARCTICA - ミウラ, サトシ; カミヌマ, カツタダ; MIURA, Satoshi; KAMINUMA, Katsutada (National Institute of Polar Research, 1988)
P(論文) Gravity surveys were carried out at 11 sites in Ross Island, Dailey Islands and the Dry Valleys during the 1986-1987 field season. Bouguer anomalies in Ross Island and Dailey Islands are nearly zero, within a few tens of mgals, whereas those in the Dry Valleys show large negative values down to -170 mgal. Therefore, the anomalies change steeply from west to east. A simple model for the crust and upper mantle around the region is proposed to explain the Bouguer anomalies. According to the model calculation, a possible interpretation of the steep variation of Bouguer anomaly up to 170 mgal is attributed to the difference in depth of the Moho discontinuity. This suggests that the depth of Moho at the Transantarctic Mountains is deeper than that beneath the McMurdo Sound by about 20km. departmental bulletin paper